Resiliensi perawat rawat inap, instalasi gawat darurat, dan intensive care unit - Wadhanti, Dewa Ayu Puspa; Rahayu, Urip; Yulianita, Henny (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Nurses are among the most vulnerable professions to stress. Workload and work environment are among the primary causes of stress for nurses in various care units. This not only affects their well-being but also impacts the quality of care provided to patients. Resilience helps nurses adapt, endure, and recover from challenging and high-pressure situations. High resilience can enhance job satisfaction and reduce the negative effects of work-related stress. V Purpose: To identify the resilience of inpatient, emergency department (ED), and intensive care unit (ICU) nurses in carrying out their daily duties. Method: A descriptive quantitative design with the nursing population at RSUD Umar Wirahadikusumah. The sampling technique used is disproportionate stratified sampling, with a total sample consisting of 38 Emergency Department (ED) nurses, 31 Intensive Care Unit (ICU) nurses, and 144 inpatient ward nurses. The study utilizes the Connor Davidson Resilience Scale (CD RISC-25) in the Indonesian language. Data analysis is conducted using univariate analysis. Results: This study shows that less than half of the nurses working in the inpatient, emergency department (ED), and intensive care unit (ICU) have moderate resilience (43.7%), while 31.5% have low resilience, and only a small percentage (24.9%) demonstrate high resilience. The lowest resilience aspect among inpatient, emergency department (ED), and ICU nurses is the coping aspect. Conclusion: Most nurses in the inpatient unit, emergency department (ED), and ICU have a moderate to low level of resilience, with coping being the lowest resilience aspect. Keywords: Emergency Department; Intensive Care Unit (ICU); Inpatient Unit; Nurse; Resilience. Pendahuluan: Perawat merupakan profesi yang paling rentan terhadap stres. Beban kerja dan lingkungan kerja menjadi salah satu penyebab utama stres bagi perawat di berbagai unit perawatan. Hal ini tidak hanya memengaruhi kesejahteraan, tetapi juga dapat memengaruhi kualitas perawatan yang diberikan kepada pasien. Resiliensi membantu perawat untuk beradaptasi, bertahan, serta bangkit dari situasi sulit dan penuh tekanan. Resiliensi yang tinggi dapat meningkatkan kepuasan kerja dan mengurangi berbagai dampak negatif akibat stres kerja. Tujuan: Untuk mengidentifikasi resiliensi perawat rawat inap, instalasi gawat darurat, dan intensive care unit. Metode: Penelitian desain deskriptif kuantitatif dengan populasi perawat di RSUD Umar Wirahadikusumah. Teknik sampling yang dilakukan adalah disproportionate stratified sampling dengan sampel penelitian, yaitu 144 perawat rawat inap, 38 perawat Instalasi Gawat Darurat (IGD), dan 31 perawat Intensive Care Unit (ICU). Penelitian ini menggunakan instrumen Connor Davidson Resilience Scale (CD RISC-25) berbahasa Indonesia. Analisis data yang digunakan adalah analisis univariat. Hasil: Penelitian ini menunjukkan bahwa kurang dari setengah perawat yang bekerja di rawat inap, IGD, dan ICU secara keseluruhan memiliki resiliensi sedang (43.7%), setengah lainnya memiliki resiliensi rendah (31.5%), dan hanya sebagian kecil memiliki resiliensi tinggi (24.9%). Aspek resiliensi terendah pada perawat rawat inap, IGD, dan ICU adalah aspek koping. Simpulan: Sebagian besar perawat di rawat inap, IGD, dan ICU memiliki tingkat resiliensi yang tergolong sedang hingga rendah dengan aspek resiliensi terendah adalah koping. Kata Kunci: Instalasi Gawat Darurat; Intensive Care Unit (ICU); Perawat; Rawat Inap; Resiliensi.